Nanobots in Pharmacy: A Futuristic Approach to Drug Delivery and Therapeutics - Shrivastava, Pranjul; Uikey, Aditya Raj; Sakharwade, Aniket; Kumar, Ankit; Meher, Amrit; Tiwari, Sandip Prasad (Journal of Neonatal Surgery, 2025)
Nanotechnology has played a significant role in the modern healthcare and medicine system, particularly through the development of nanobots, which have revolutionized the field of pharmaceutical drug delivery and cancer therapy. Nanobots are tiny robotic devices that, when implanted in the human body, move within biological systems to cancer cells and release therapeutic drugs with the highest accuracy. These devices allow the most targeted therapy approach, limiting the effect of drugs to healthy tissues, reducing systemic side effects, and enhancing treatment output. Furthermore, nanobots can be used to design a real-time monitoring system, early detection, and drug release, which are effective for cancer therapy. This review paper shows the design and implementation potential of such nanobot devices, highlighting their mechanisms, advancements and future prospects